Emergence of Streptococcus suis infection from Goa, India - Hanul Thukral; Simmi Tiwari; Ajit Shewale; Tushar Nale; Kedareshwar Narvencar; Prashant Suryawanshi; Trudy Fernandes (CABI One Health, 2024)
Abstract Streptococcus suis is an emerging zoonotic bacterium that causes severe invasive disease in humans. In India, only two human case reports have been recorded till now. In the present report, we described the clinical case report along with an epidemiological investigation of the first S. suis case from Goa, India. The clinical presentation and detailed history regarding the potential exposure factors for the infection were recorded and to trace the source of the infection, the meat markets and the backyard piggeries in the vicinity of the patient’s residence were investigated. Case definitions were formulated and enhanced surveillance was initiated in the State to identify any additional cases. The case-patient was a co-morbid 63-year-old female, who was provisionally diagnosed with meningitis and septicaemia and S. suis infection was detected using automated microbial identification systems. The epidemiological investigation revealed that the patient was involved in handling raw pork one day prior to the symptom onset. Based on the active case finding, no additional case of S. suis was detected in the area. The present case was a sporadic case of S. suis in Goa, India and case-patient may have been exposed to the bacteria by handling raw pork while cooking. One Health impact statement Our investigation described the 3rd case of Streptococcous suis from India. This is significant because despite the abundance of the source of infection across the country i.e. high prevalence in the pig population, there are unusually low number of human cases, which can be attributed to very low clinical index of suspicion and lack of diagnostic tests in humans, as evidenced in the present case. A multi-disciplinary One Health approach has been applied for the present case investigation as the Human Health, Animal Health and Food Safety aspects were investigated in collaboration with the State Health & Animal Husbandry departments along with the academia. The findings of the present investigation will aid in enhancing the clinical index of suspicion among clinicians and awareness among high-risk groups like veterinarians for S. suis infection in humans and animals. The multi-disciplinary One Health approach aided us in tracing the source of the infection, which would help in generating evidence for designing preventive interventions.